Предмет: Алгебра,
автор: sambist111
а) (с-2) (с+3)-(с-1)^2
б) 3(а+с)^2-6ас
в) (р-3) (р^2+3р+9)-р^3
Пожалуйста Помогите Мне
Ответы
Автор ответа:
1
а) (с-2)*(с+3)-(с-1)²=с²+3с-2с-6-(с²-2с+1)=с²+3с-2с-6-с²+2с-1=3с-7
б) 3(а+с)²-6ас=3(а²+2ас+с²)-6ас=3а²+6ас+3с²-6ас=3а²+3с²
в) (р-3)*(р²+3р+9)-р³=р³+3р²+9р-3р²-9р-27-р²=р³-р²-27
б) 3(а+с)²-6ас=3(а²+2ас+с²)-6ас=3а²+6ас+3с²-6ас=3а²+3с²
в) (р-3)*(р²+3р+9)-р³=р³+3р²+9р-3р²-9р-27-р²=р³-р²-27
sambist111:
спасибо
Похожие вопросы
Предмет: Русский язык,
автор: Turi007
Предмет: Русский язык,
автор: Серебролапая
Предмет: Українська література,
автор: budanovaanastasia
Предмет: Биология,
автор: unicorn926